Antagonist effect of probiotic bifidobacteria on biofilms of pathogens associated with periodontal disease - Argandoña Valdez, Remberto Marcelo [UNESP]; Ximenez-Fyvie, Laurie ann; Caiaffa, Karina Sampaio [UNESP]; Rodrigues dos Santos, Vanessa [UNESP]; Gonzales Cervantes, Rina Maria; Almaguer-Flores, Argelia; Duque, Cristiane [UNESP] (Elsevier, 2021)
The in vitro antagonist growth effect of bifidobacteria were evaluated on periodontal bacteria. Bifidobacterium longum, Bifidobacterium lactis and Bifidobacterium infantis biofilms were grown in single, double or triple combinations with putative periodontal pathogens P. gingivalis and F. nucleatum or beneficial bacteria S. oralis for 24, 72 and 168 h and the total counts were analyzed by checkerboard DNA-DNA hybridization. The results showed that B. infantis and B. lactis, as single species, demonstrated the best antagonist effect on F. nucleatum and P. gingivalis and no influence on S. oralis growth at 168 h. All the double combinations of bifidobacteria tested demonstrated an inhibitory effect on F. nucleatum (72 h) and P. gingivalis (168 h) and did not affect S. oralis counts at any time. In conclusion, B. lactis and B. infantis alone or in double combinations have antagonist effect on periodontopathogens biofilms, at different time points, and minimal influence on S. oralis growth.
Keywords: Bifidobacterium; Biofilms; Checkerboard DNA-DNA hybridization; Fusobacterium nucleatum; Porphyromonas gingivalis